2010
DOI: 10.1182/blood-2009-07-231985
|View full text |Cite
|
Sign up to set email alerts
|

AR-42, a novel HDAC inhibitor, exhibits biologic activity against malignant mast cell lines via down-regulation of constitutively activated Kit

Abstract: Histone hypoacetylation occurs in many cancers and inhibition of histone deacetylation is a promising approach to modulate these epigenetic changes. Our laboratory previously demonstrated that the histone deacetylase inhibitors (HDACis) vorinostat and AR-42 reduced the viability of a canine malignant mast cell line. The purpose of this study was to further investigate the mechanisms of pan-HDAC inhibition in normal and malignant mast cells. Mouse and canine malignant mast cell lines expressing various Kit muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
62
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 40 publications
6
62
0
1
Order By: Relevance
“…20,29,38 Mutations result in constitutive activation of KIT, initiating signaling cascades leading to proliferation, survival, and invasion. 9,[15][16][17][18]21,22,29 One group reported that the presence of ITD mutations of c-KIT or aberrant cytoplasmic KIT protein localization was significantly associated with higher values of Ki67. 37 It is not clear from any study of cutaneous MCT if subcutaneous MCT were included; if so, the data could be compromised.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…20,29,38 Mutations result in constitutive activation of KIT, initiating signaling cascades leading to proliferation, survival, and invasion. 9,[15][16][17][18]21,22,29 One group reported that the presence of ITD mutations of c-KIT or aberrant cytoplasmic KIT protein localization was significantly associated with higher values of Ki67. 37 It is not clear from any study of cutaneous MCT if subcutaneous MCT were included; if so, the data could be compromised.…”
mentioning
confidence: 99%
“…6,9,11,[14][15][16][17][18][19][20][21][22]29,[36][37][38] Studies show that up to 30% of dogs with MCT have mutations in the juxtamembrane domain, 6,9,20,22,29,37,38 the majority of which are internal tandem duplications (ITD) in exon 11. The presence of these mutations is associated with higher-grade tumors.…”
mentioning
confidence: 99%
“…The major mechanism of HDACIs is believed to be through changes in the transcription of several genes involved in proliferation and cell cycle regulation. In particular, AR42 upregulates expression of p21 (40,41). This protein is known to bind to CDK/cyclin complexes and decrease kinase activation, which leads to cell accumulation in the S and G2/M.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most canine cases with MCTs eventually undergo relapses even after achievement of a remission with TKIs treatment. Therefore, the efficacy of several novel agents such as HSP90 inhibitor [17], HDAC inhibitors [13,18] and calcitriol which is the ligand for vitamin D receptor [24] for canine MCT have recently been examined.Our previous study revealed that the c-KIT receptor of VIMC1 cells, a MCT cell line harboring a point mutation in the extracellular domain of KIT, was consistently phosphorylated in ligand-free medium [33]. Another our study subsequently indicated that the concentration of some TKIs required for inhibition of the phosphorylation of c-Kit receptor was higher than that of cell growth in VIMC1 cells [32].…”
mentioning
confidence: 99%
“…In addition, most canine cases with MCTs eventually undergo relapses even after achievement of a remission with TKIs treatment. Therefore, the efficacy of several novel agents such as HSP90 inhibitor [17], HDAC inhibitors [13,18] and calcitriol which is the ligand for vitamin D receptor [24] for canine MCT have recently been examined.…”
mentioning
confidence: 99%